CogSport: reliability and correlation with conventional cognitive tests used in postconcussion medical evaluations - Collie, A.; Maruff, P.; Makdissi, M.; Mc Corry, P.; Mc Stephen, M.; Darby, D. (Clinical Journal of Sport Medicine, 2003)
Objective: To determine the repeatability of a computerized cognitive test designed to monitor recovery from concussion and assist team physicians make return to play decisions (CogSport™). To determine the correlation between CogSport and two conventional neuropsychological tests. Design: Prospective, serial investigation of cognitive function. Setting: Professional and semi-professional Australian Football clubs and a university affiliated research institute in Melbourne, Australia. Participants: Three-hundred healthy young adults, including 240 elite athletes. Main Outcome Measures: Intra-class correlation (ICC) coefficients for CogSport performance measures administered serially. ICC between CogSport performance measures and conventional neuropsychological tests. Normative data for CogSport performance measures. Results: Measures of psychomotor function, decision making, working memory and learning were highly reliable. Some measures also displayed high correlations with conventional neuropsychological tests of information processing and attention. Preliminary normative data is described. Conclusions: CogSport is a highly reliable cognitive function test when administered to healthy young adults and elite athletes. CogSport measures similar cognitive functions as conventional tests used commonly in concussion research.